Analisis Interaktivitas Akun @Awaskbgo Dalam Mengadvokasi Isu Kekerasan Berbasis Gender Online Di Instagram - Putri Namira, Amadhea; Nurliah (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
With the development of the internet, social media is present as a space for exchanging information online, nowadays social media not only be used as a personal account, but also can be used as an advocacy media account. The @awaskbgo account is an account that advocates for the issue of online gender-based violence in Indonesia. For this reason, the purpose of this study is to describe and explain the interactivity on social media to activities against online gender-based violence on the @awaskbgo Instagram account and to see how social media becomes a forum for advocacy. This type of research is a qualitative method with a descriptive approach. With a focus on writing, draws from three elements of interactivity, namely, user to system, user to user & user to document. The results of this study found the use of the Instagram algorithm in increasing user-to-system interactivity, but user-to-user and user-to-document interactivity has not been maximized in increasing the interactivity of the @awaskbgo account.